Assessment Of Athlete Concentration Via Application: Validity, Reliability And Categorization - Hambali, Sumbara; Hardi, Veny Juniarni (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The purpose of this study was to determine the feasibility of athletes' concentration instruments by finding their validity and reliability levels and categorizing their concentration levels. The method used is quantitative descriptive with a survey approach and uses a type of trial design. The subjects of this study were 20 sports students who were members of the Handball Student Activity Unit at STKIP Pasundan. The instrument tested is a concentration test in the Concentration Grid Test (CGT) application developed by the Stalwart Group LLC company with a total of 36 boxes, consisting of 6 rows and 6 columns. The research data was collected using the test method, where the test was carried out as many as two repetitions. This type of data analysis uses the Pearson correlation method approach for validity, which analyzes the data of the first test result with the average of the test results, while for reliability it uses the test-retest technique and for the determination of categorization using the interval class length search approach technique. The results of the study found that the validity value for this instrument is r = 0.980 and the value for reliability is r = 0.931, so this is included in the very high category. As for the categorization, it is divided into five categories, namely very good, good, medium, less and less once.